Research on the Innovation and Entrepreneurial Ability of Chinese College Students in the Perspective of Cultural and Creative Industries - Zhang, Jianying; Carrido, Mary Grace P. (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
With the continuous development of economy, an increasing number of college students with entrepreneurial enthusiasm has emerged in contemporary society, and to a certain extent, the entrepreneurial spirit of college students contains the level and quality of education in Chinese universities. This article mainly analyzes the innovation and entrepreneurship ability of Chinese college students in cultural and creative industries. The article adopts the method of data analysis and induction to analyze the innovation and entrepreneurship of college students from political, economic, cultural, professional and technical aspects of Strengths-Weaknesses-Opportunities-Threats (SWOT) 4 dimensions, and summarizes the opportunities and challenges college students are facing in entrepreneurship. Through the research data, this article hopes provide suggestions and help for college students who are engaged in or planning to engage in innovative entrepreneurship.